Analytische Lösungen einer Klasse linearen Gleichungen mit partiellen Ableitungen - Kisielius, J. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. В. Киселюс. Аналитические решения одного класса линейных уравнений в частных производныхJ. Kisielius. Vienos tiesinių lygčių su dalinėmis išvestinėmis klasės analiziniai sprendiniai